A MOF-derived method to construct well-arranged porous nanosheets for lithium ion batteries. Issue 22 (23rd May 2018) - Du, JinCheng; Tang, YuHai; Wang, Yu; Shi, PengHui; Fan, JinChen; Xu, QunJie; Min, YuLin
Abstract : In this work, we report a facile route to fabricate a ZnCo2 O4 nanosheet derived from metal–organic frameworks. Abstract : In this work, we report a facile route to fabricate a ZnCo2 O4 nanosheet derived from metal–organic frameworks. The as-prepared ZnCo2 O4 nanosheet material for lithium-ion batteries shows an excellent electrochemical performance. The obtained ZnCo2 O4 nanosheet delivers a high reversible capacity of 1640.8 mA h g −1 at a current density of 100 mA g −1 after 50 cycles. More importantly, even at a current density of 1500 mA g −1, the electrode material still exhibits a discharge capacity of 581.3 mA h g −1 after 190 cycles. These results demonstrate that the ZnCo2 O4 nanosheet shows great potential as an anode material for lithium ion batteries.